(untitled) (Cardiovascular Journal, 2020)
Background: Coronary artery disease is an important medical and public health issue as it is common and leading cause of mortality and morbidity in Bangladesh as it is throughout the world. This study was carried out to determine the existence of seasonal rhythms in hospital admissions due to acute myocardial infarction (AMI) in Dhaka Medical College Hospital. Methods: This cross-sectional observational study was conducted during the period of April 2015 to March 2016 among the patients with AMI admitted at the Cardiology Department of DMCH. 882 patients were enrolled. Results: The highest number of patients were admitted during winter (n=285, 32.3%) followed by post monsoon (n=213, 24.1%) and monsoon (n=194, 22.0%). The lowest number of patients were admitted during summer (n=190, 21.5%). The hospital admission was significantly higher in winter compared to other seasons (p-value versus summer, monsoon and post monsoon was 0.008, 0.011 and 0.042 respectively). Conclusion: A seasonal variation in the hospital admission due to AMI with a peak in winter was clearly demonstrated in the study. Persons admitted to hospital with AMI tend to be all age groups and both sexes present a stronger seasonal variation peak admission in winter. Cardiovasc. j. 2020; 12(2): 126-134